2011
DOI: 10.3892/etm.2011.187
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of co-expression of STAT3, mTOR and EGFR in gastric cancer

Abstract: Abstract. Signal transducer and activator of transcription 3 (Stat3), the mammalian target of rapamycin (mtOr) and epidermal growth factor receptor (EGFr), proteins that mediate intracellular signaling related to cell growth, proliferation and differentiation, have received considerable interest as possible targets for cancer treatment. We examined whether the expression of Stat3, mtOr and EGFr correlates with clinicopathological features and patient outcome in gastric cancer. tumor samples were obtained from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 29 publications
0
13
0
1
Order By: Relevance
“…Indeed, EGFR has been throughout investigated, although its role as prognostic factor remains controversial. In several studies the expression of EGFR was shown to be related with the survival of GC patients and associated with an adverse prognostic value [99][100][101][102] . However, recent studies found that positive EGFR expression is not prognostic of patient outcome in GC patients [103][104][105] .…”
Section: Therapeutic Approachesmentioning
confidence: 99%
“…Indeed, EGFR has been throughout investigated, although its role as prognostic factor remains controversial. In several studies the expression of EGFR was shown to be related with the survival of GC patients and associated with an adverse prognostic value [99][100][101][102] . However, recent studies found that positive EGFR expression is not prognostic of patient outcome in GC patients [103][104][105] .…”
Section: Therapeutic Approachesmentioning
confidence: 99%
“…Experimental evidence also suggest EGFR amplification to result in a less favourable prognosis [33,35]. However, similar to previous reports, some of the over expressing cases of GTD have also registered negative for presence of gene amplification suggesting that there are multiple mechanisms involved in EGFR protein over expression [37] and alterations of the gene secondary to amplification may be important toward the oncogenic effect of EGFR [38,39].…”
Section: Discussionmentioning
confidence: 68%
“…Reviewers identified 56 potential studies for full-text review and 31 studies were eliminated due to inadequate data for meta-analysis. Finally, 25 studies were included in the current meta-analysis [7, 9, 10, 1940]. The detail of the screening process was shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…The prognostic significance of EGFR expression in GC patients was controversial in different studies. High EGFR expression has been reported to be correlated with poor prognosis in patients with GC [78]. However, it has been reported that patients with high EGFR expression had favorable prognosis than those with low EGFR expression [9].…”
Section: Introductionmentioning
confidence: 99%